Gastrointestinal Motility Disorders A Point of Care Clinical Guide (Springer International Publishing, 2018)
This guide focuses on the answers to patient questions that are frequently posed to providers who care for patients with GI motility disorders. Additionally, the text guides clinicians through the complicated diagnostic and therapeutic/management approaches to motility disorders, including common and specialized tests, drug initiation, medications side effects, and disease complications. Written by experts in the field, Gastrointestinal Motility Disorders: A Point of Care Clinical Guide is a valuable reference for busy clinicians who need the best evidence-based answers to patient questions at their fingertips.